Inadequate Care During the Management of Type-2 Diabetes Mellitus: Prevalence and Associated Characteristics - Syed Bakht Ruidar, Zainab Rizwan, Amir Bashir, Nadiya Khan, Muhammad Sajid Khan, Yasir Mansoor (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to provide light on the reasons for and outcomes of inadequate treatment for type 2 diabetes. Study Design: Retrospective study Place and Duration: This Retrospective study was conducted at Fazaia Medical College Islamabad in the period from May, 2022 to October, 2022. Methods: Total 178 patients of T2 diabetes mellitus were presented. Age of the included cases were between 20-70 years. Informed written consent was obtained from all participants before to recording their demographic information, which included details such as comorbidities, body mass index (BMI), age, and smoking status. Lifestyle management, vaccination, pharmaceutical therapy, laboratory assessment, and physical examination are the five areas used to define inadequate care. SPSS 22.0 was used to analyze all data. Results: In all, ninety-eight (55.1%) cases were males and eighty (44.9%) cases were females. The mean age among patients was 53.13±5.44 years having mean BMI 26.11±6.76 kg/m2. Majority of the cases 78 (43.8%) were had poor socio-economic status. 45 (25.3%) cases were smokers and HTN was found in 76 (42.7%) cases. Frequency of inadequate life style management 44 (24.7%), inadequate immunization 60 (33.7%), inadequate pharmacological therapy 80 (44.9%), inadequate physical examination 72 (40.4%) and inadequate laboratory tests were 48 (26.96%). Overall inadequate care was found in 135 (75.8%) cases. Conclusion: Treatment of type 2 diabetes is plagued by widespread problems due to inadequate care. It was shown that over 75.8% of people experienced at least one form of subpar care out of a possible five. Systematic, medical professional, and individual variables were all linked to subpar care delivery. Keyboards: T2 DM, Adherence and Compliance, Diabetes Care